Software industry awareness on green and sustainable software engineering: a state-of-the-practice survey - Karita, Leila; Mourão, Brunna C.; Machado, Ivan (Anais do Simpósio Brasileiro de Engenharia de Software (SBES); 2019: Anais do XXXIII Simpósio Brasileiro de Engenharia de Software, 2019)
Sustainable computing is a rapidly growing research area spanning several areas of computer science. In the software engineering field, the topic has received increasing attention in recent years, with several studies addressing a range of concerns. However, few studies have demonstrated the awareness of software practitioners about the underlying concepts of sustainability in the software development practice. In this effect, in this study, we aim to provide some evidence about the practitioners' perception about the adoption of sustainability in software development, under four main perspectives: economic, social, environmental and technical. To accomplish such a goal, we carried out a survey study with twenty-five software engineers involved in projects in different domains. The yielded results indicate an overall lack of knowledge about the topic, in particular regarding the concepts about sustainable software, although it is a common understanding that sustainability should be treated as a quality attribute and should support the interaction between sustainability and the software development life cycle phases. Among the observed perspectives, the respondents indicate that the technical dimension is the most relevant and explored so far. This study contributes to the field with initial evidence and can be seen as a first step towards establishing a common understanding about how the software industry is receptive to the use of sustainability concepts in software development practices.